Penerapan Media Edukatif untuk Meningkatkan Kesadaran Pengelolaan Sampah pada Siswa SD Negeri Jambewangi, Kecamatan Pakis, Kabupaten Magelang - Wisnu Satrio Amaanulaah Akmal; Abdullah Rasyid; Lailani Amalia; Nofithania Syawalaila Ayusandrina; Wakhidatul Arifah; Sulistyowati Sulistyowati; Khusna Zulfatul Arifah; Muhammad Herfa Setiawan; Galang Adri Saputra; Verdhi Adnan Qur Rachim; Olivia Wardhani (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
Schools are not only institutions for the transfer of knowledge but also environments that play a crucial role in shaping students’ behavior and instilling positive habits, one of which is environmental care. One form of environmental concern that can be cultivated from an early age is the discipline of disposing of waste properly. However, SD Negeri Jambewangi, located in Dusun Pesantren, has not yet fully implemented effective waste sorting practices. Waste disposal is still carried out without distinguishing between organic and inorganic waste, which may have negative impacts on the school environment. To address this issue, community service activities were carried out by KKN students from Universitas Tidar through outreach programs and the distribution of sorted waste bins. The socialization activity applied the Extend Parallel Process Model (EPPM) communication strategy using a Severity Model approach, which emphasized the dangers and consequences of improper waste management practices. During the sessions, students were encouraged to discuss and identify various types of waste, as well as the potential environmental and health impacts associated with them. Direct practice was also provided by encouraging students to actively participate in sorting waste before disposal into the designated bins. The implementation of this program showed a positive impact, as students demonstrated an increased understanding of waste management and began to practice sorting waste more consistently. The provision of separate bins for organic and inorganic waste further facilitated this new habit. It is expected that the discipline of sorting and properly disposing of waste will continue to be applied by students, teachers, and the entire school community. Such continuous practices can foster collective awareness, contribute to maintaining environmental cleanliness, and provide long-term benefits not only for the school but also for the surrounding community.